Factors Influencing the Processed Pineapple Export Competitiveness of Thailand - Thanet Wattanakul; Sakkarin Nonthapot; Tanawat Watchalaanun (Australasian Accounting, Business and Finance Journal, 2021)
This study aims to explore the factors influence the competitiveness of Thailand’s processed pineapple exports as well as the impact size of these factors by focusing on canned pineapple (HS 200820) and pineapple juice (HS 200949). This study also determine the competitiveness and market share effects for both products in each market in each Thailand major partner countries. The average price of processed pineapple, GDP per capita and exchange rate were the explanatory variables. The panel data from 2013 to 2017 of 10 partners were used in a panel regression model with pooled OLS, fixed effect and random effect models. The empirical results show that the fixed effect model is the most suitable and that price significantly negatively affected the market share of both products. Moreover, there is a positive effect from GDP per capita on market share for pineapple and the exchange rate positively affected market share for canned pineapple. In addition, Thailand’s pineapple juice market share is less price sensitive than the canned pineapple market. The stable and competitive price are necessary conditions to enhance sustainable export competitiveness under current intense competition. The implementation of effective exchange rate management to prevent massive fluctuation is a crucial supporting mechanism to achieve this target. Moreover, the appropriate devaluation is other essential policy to enhance sustainable price competition under the tension competitive environment leads to accelerate the continue market shares in important markets.
Keywords: Processed Pineapple; Pineapple Juice; Canned Pineapple; Market Share; Export Competitiveness